Functional Knee Stability in Elite Field Hockey Depends on Playing Class and Gender - Hiepen, Lucie; Bosserhoff, Niklas; Schaudig, Florian; Heitzer, Falko; Jäger, Marcus; Mayer, Constantin (Sports Medicine International Open, 2025)
Field hockey, a physically demanding Olympic sport, carries a high risk of lower limb injuries, yet data on injury risk in elite field hockey are limited. Functional knee stability is important for injury prevention and a safe return to sport. This study is the first to investigate functional knee stability in elite field hockey, considering gender and playing class, and establishes reference data for functional knee stability by using a standardized test battery that assesses one- and two-legged stability, jumping tests, speed, and agility. Seventy-two elite field hockey players, 30 males and 42 females (age 19.82±3.74 years) were divided into High Playing Class (HPC) and Moderate Playing Class (MPC). HPC players showed significantly better performance in all functional tests except balance tests (p<0.01–0.024). Females showed significantly better one- and two-leg stability (p<0.01) with lower injury rates, indicating the relevance of gender considerations. The study emphasizes the importance of balance and stability in the prevention of lower limb injuries in Olympic field hockey and also highlights the importance of considering pre-existing deficits in functional knee capability when assessing athletes for return to sport. These results can help improve athletic performance, identify individual strengths and weaknesses, prevent injury or re-injury, and facilitate return to sport after injury.
Keywords: knee function; functional test battery; return to sport criteria; field hockey; reference data